2011
DOI: 10.1111/j.1600-0501.2010.02094.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of SLActive surface in guided bone formation in osteoporotic-like conditions

Abstract: The use of modSLA surface may promote bone healing and osseointegration in osteoporotic rabbits, whereas administration of bisphosphonates may compromise the osseointegration of the newly formed bone at the early healing period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
62
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 56 publications
7
62
0
Order By: Relevance
“…Regarding crestal circumferential bone defects (circumferential gap, width 0.5-1 mm, height 5 mm), it has also been shown that BIC and new bone fi ll were signifi cantly increased after 2 and 4 weeks but not after 8 weeks on modSLA implants compared to SLA implants placed in canines [ 148 ]. Even when comparing both types of implants in rabbits with experimentally induced osteoporosis, mod-SLA signifi cantly increased new bone healing (indicated by newly formed bone, newly formed mineralized bone, BIC) after 30 and 120 days of investigation compared to SLA [ 150 ]. Thus, the excellent osteoconductive properties of the mod-SLA implant surface were not only demonstrated around implants placed in bone defect areas but also when investigating peri-implant crestal bone levels in non-defect areas and in different animal models.…”
Section: Modsla: Bone Tissue Regenerationmentioning
confidence: 89%
“…Regarding crestal circumferential bone defects (circumferential gap, width 0.5-1 mm, height 5 mm), it has also been shown that BIC and new bone fi ll were signifi cantly increased after 2 and 4 weeks but not after 8 weeks on modSLA implants compared to SLA implants placed in canines [ 148 ]. Even when comparing both types of implants in rabbits with experimentally induced osteoporosis, mod-SLA signifi cantly increased new bone healing (indicated by newly formed bone, newly formed mineralized bone, BIC) after 30 and 120 days of investigation compared to SLA [ 150 ]. Thus, the excellent osteoconductive properties of the mod-SLA implant surface were not only demonstrated around implants placed in bone defect areas but also when investigating peri-implant crestal bone levels in non-defect areas and in different animal models.…”
Section: Modsla: Bone Tissue Regenerationmentioning
confidence: 89%
“…13 In addition, in other preclinical studies, reduction of bone mechanical properties, 14,15 formation of impaired extracellular matrix (ECM) and delay of bone healing [16][17][18] have been shown. However, the use of implants with modified, hydrophilic surfaces treatment has shown to significantly improve dental implant success in osteoporotic animals 19,20 and should be further investigated in future human studies. 21,22 Even though few prospective and retrospective clinical studies indicated that osteoporosis could impair implant success, 5,23-25 a systematic and a critical review on this topic concluded that there is not enough evidence to consider osteoporosis as an absolute contraindication for implant placement.…”
Section: Osteoporosismentioning
confidence: 97%
“…A major target of implant surface modification is to accelerate and improve osseointegration. Sandblasted and acid-etched titanium surfaces reportedly accelerated and promoted osseointegration and increased boneimplant contact areas 29,30) . Such improvements were reportedly brought about by an increase in hydrophilicity and a decrease in adsorbed hydrocarbons at the surface.…”
Section: Discussionmentioning
confidence: 99%